2015
DOI: 10.1007/s13277-015-3168-x
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between TGF-β1 gene 29 T > C single nucleotide polymorphism and clinicopathological characteristics of osteosarcoma

Abstract: Transforming growth factor (TGF)-β1 is the most abundant growth factor in human bone. Several polymorphisms have been described in the TGF-β1 gene. To explore the correlation between TGF-β1 gene single nucleotide polymorphism and the clinicopathological characteristics of osteosarcoma. TaqMAN PCR technique was used to detect the TGF-β1 gene polymorphism of 124 patients with osteosarcoma from last follow-up and 136 healthy controls. The difference of gender, age, and allele frequency between patient group and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…Thus, it plays a key role in chronic HBV infection-induced liver inflammation and fibrosis. At present, many studies have also examined the molecular structure of TGF-β1 to define the relationship between TGF-β1 and HBV from a perspective of gene polymorphisms [ 84 ]. However, many of the results are inconsistent and unsatisfactory because of ethnic and geographical differences and case selection bias.…”
Section: New Anti-hbv Drugs Under Development and Evaluationmentioning
confidence: 99%
“…Thus, it plays a key role in chronic HBV infection-induced liver inflammation and fibrosis. At present, many studies have also examined the molecular structure of TGF-β1 to define the relationship between TGF-β1 and HBV from a perspective of gene polymorphisms [ 84 ]. However, many of the results are inconsistent and unsatisfactory because of ethnic and geographical differences and case selection bias.…”
Section: New Anti-hbv Drugs Under Development and Evaluationmentioning
confidence: 99%
“…A total of nine studies [ 26 , 29 , 32 , 33 , 36 40 ] with 1119 cases and 1358 controls were recruited in this meta-analysis. The process of study selection and the inclusion process are shown in Figure 1 .…”
Section: Resultsmentioning
confidence: 99%
“…Oliveira et al [ 26 ] and Xie et al [ 37 ] studied the relationship between TNF-β 252A/G and susceptibility to OS. Ma et al [ 38 ], Xu et al [ 39 ] and Wu et al [ 40 ] reported the alleles and genotypes of TGF-β1 29T/C polymorphism. Oliveira et al [ 26 ] reported the alleles and genotypes of IL-6 174G/C and IL-10 1082A/G polymorphism, and these two polymorphisms were also studied by Qi et al [ 32 ] and Cui et al [ 33 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations